The Effect of Product Quality, Service Quality, Price, and Location on Purchase Decisions at Roti Ropi Delanggu, Klaten Regency - Azzahra, Mutiara Sintya; Rohmah, Fatkhiyah; Nugraha, Widya Satya (Politeknik Negeri Jember, 2025)
This research aims to analyze the simultaneous and partial impacts of Production Quality, Service Quality, Price, and Location on purchasing decisions at Roti Kopi Delanggu in Klaten Regency. Data in this research were collected directly from respondents through a questionnaire using a nonprobability sampling technique with incidental sampling, resulting in a sample size of 50 respondents. The analysis methods employed included multiple linear regression, coefficient of determination, F-tests, and t-tests, along with validity, reliability, and classical assumption tests. IBM SPSS 26 for Windows was utilized as the analysis tool. The results indicated a regression equation of Y = 7.004 + 0.064 X1 + 0.429 X2 + 0.164 X3 + 0.085 X4 + e, showing that the independent variables accounted for 32.9% of the variance in purchasing decisions (Y). The F-test revealed that Product Quality, Service Quality, Price, and Location collectively influenced purchasing decisions. However, the t-test results indicated that Product Quality, Price, and Location had insignificant effects, while Service Quality had a significant impact on purchasing decisions.